Interculturele competentie in het universitair onderwijs in Nederlands als vreemde taal - Buczak, Mikolaj (Lage Landen Studies, 2025)
The value of intercultural competence in everyday life is undeniable. It expands our cognitive horizons, fosters openness to others, and enables us to recognize and critically analyze cultural differences and similarities. In foreign language teaching, intercultural reflection contributes to a deeper understanding of cultural and linguistic diversity in the modern world. This study focuses on strengthening intercultural skills in the teaching of Dutch as a foreign language. Using a mixed methodology, Mikołaj Buczak investigates how many bachelor's students in Dutch Studies at the University of Wrocław, Adam Mickiewicz University in Poznań, and John Paul II Catholic University in Lublin develop their intercultural competence. He also examines how this development is supported during practical Dutch courses at these Polish universities. The results offer insight into the role of the intercultural component within the complex context of international Dutch Studies.